ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS DAN RASIO LIKUIDITAS PADA PT. PANCA USAHA MAKMUR - Nurhaliza; Rozi, Facrul (PT. ANAN PUBLISHER CENDEKIA, 2024)
The purpose of this research is to find out the financial performance of the PT. Panca Usaha Makmur in the years 2019–2021. The types of data used in the research are primary data and secondary data. This research uses a descriptive approach, i.e., a method performed by collecting, classifying, analyzing, and interpreting data related to the problem encountered and comparing the secondary information obtained with the actual situation in the company to draw conclusions. Based on the data analysis, the financial performance through the profitability ratio and the liquidity ratio at the P.T. Panca Usaha Makmur is very poor, where the value of each ratio is below the average. Return on assets in 2019 was 0.01%, in 2020 it was 0.046%, and in 2021 it was 0.036%. Return on equity in 2019 at 3.40%, in 2020 at 9.57%, and in 2021 at 5.88%. The current ratio in 2019 is 0.58%; in 2020, it is 0.51%; in 2021, it is 0.80%. Cash ratio was 0.49% in 2019, 0.35% in 2020, and 0.55% in 2021. This makes the company need to make improvements as well as improvements for the sustainability of good financial performance of the company.